Stability improvement of a laser-accelerated electron beam and the pulse width measurement of the electron beam - Kotaki, H.; Mori, M.; Hayashi, Y.; Kando, M.; Daito, I.; Fukuda, Y.; Pirozhkov, A.S.; Koga, J.K.; Bulanov, S.V. (Вопросы атомной науки и техники, 2012)
Laser wakefield acceleration has the possibility to generate an ultrashort electron beam of the order of femtoseconds or less. In applications of these laser accelerated electron beams, stable and controllable electron beams are necessary. A high stability electron bunch is generated by laser wakefield acceleration with the help of a colliding laser pulse (optical injection). Stable and monoenergetic electron beams have been generated in the self-injection scheme of laser acceleration by using a Nitrogen gas jet target. The electron interaction with the laser field results in transverse oscillations of the electron beam. From the electron oscillation period dependence on the electron energy we find that the electron beam width is equal to 1.7 fs (rms). В процессе ускорения кильватерными волнами возможна генерация сверхкоротких электронных пучков фемтосекундной длительностью. Для приложений требуются электронные пучки с воспроизводимыми и котролируемыми параметрами. Оптическая инжекция, использующая сталкивающиеся лазерные импульсы, обеспечивает высокую воспроизводимость параметров пучков ускоренных электронов. Моноэнергетические пучки электронов с воспроизводимыми параметрами были получены при «самоинжекции» в кильватерную волну в экспериментах, использующих в качестве мишени струю азота. Взаимодействие электронов с излучением лазерного импульса приводит к поперечным осцилляциям электронного пучка. Анализ наблюдаемой в эксперименте зависимости периода осцилляций от энергии электронов позволяет найти длительность электронного пучка, равную 1.7 фс. В процесі прискорення кільватерними хвилями можлива генерація надкоротких електронних пучків фемтосекундної тривалості. Для додатків потрібні електронні пучки з відтворюючими і котролюючими параметрами. Оптична інжекція, що використовує зіштовхуючі лазерні імпульси, забезпечує високу відтворюваність параметрів пучків прискорених електронів. Моноенергетичні пучки електронів з відтворюваними параметрами були отримані при «самоінжекції» в кільватерну хвилю в експериментах, в яких в якості мішені використовувалася струмінь азоту. Взаємодія електронів з випромінюванням лазерного імпульсу призводить до поперечних осциляцій електронного пучка. Аналіз спостерігаючої в експерименті залежності періоду осциляцій від енергії електронів дозволяє знайти тривалість електронного пучка, яка дорівнює 1.7 фс.